Durango Street - Bonham, Frank (New York : Puffin, 1999)
As headman of his teenage gang, Rufus Henry has to deal not only with other gangs, but also with the police sanctioned sponsor who has involved himself with Rufus and his friends.
Previously published: E.P. Dutton, 1965.
Booklist.
Horn Book.
Notable/Best Books (A.L.A.).
5.8
5-8
Keywords: Gangs -- Fiction; Gangs -- Fiction